The Influence of Integrated Value Variables on the Repurchase Intention of Virtual Items in the Online Game Mobile Legends: Bang-Bang - Durotun Nafisah; Lia Nirawati (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study is predicated on the phenomenon of virtual item purchases in games becoming increasingly dominant. The online game Mobile Legends: Bang Bang generates revenue through in-app purchases of virtual items. Despite a decline in the number of players, the game's revenue remains relatively stable. This study aims to analyze the influence of integrated value variables, which consist of enjoyment value (X1), character competency value (X2), monetary value (X3), and visual authority value (X4), on the repurchase intention (Y) of virtual items in Mobile Legends: Bang Bang. Employing a quantitative research method, the study's population comprises active Mobile Legends: Bang Bang players who have played for at least one season. 100 respondents make up the sample size, which was chosen by a purposive sampling technique combined with non-probability sampling. Data analysis was conducted using the Statistical Product and Service Solutions (SPSS) software version 26. The findings of this study demonstrate that, simultaneously, enjoyment value, character competency value, monetary value, and visual authority value significantly influence repurchase intention. However, when examined individually, these variables do not have a significant influence on repurchase intention.